Analisis dan Reduksi Waste pada Industri Tahu Skala UKM - Citra Indah Asmarawati; Elva Susanti; Sadiq Ardo Wibowo (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Seeing the condition of the covid pandemic which is still engulfing most of the world to Indonesia which will have an impact on various aspects, both social and economic. The socio-economic impact is felt in the lower middle class. Failure to fulfill nutrients in food can have an impact on various things such as decreased intelligence, poor health and endurance. Protein sources derived from vegetables are predicted to have nutritional content that is not inferior to prices that are relatively cheaper and easy to obtain. The popularity of this tofu causes the tofu industry to be very large and spread across various regions in Indonesia. The tofu industry in Indonesia is still dominated by home-scale industries with very traditional processes using simple equipment. Lean manufacturing can be used as a method to optimize the production process by eliminating waste. By using lean manufacturing, waste will be eliminated in tofu production activities.